An empirical study of the performance of South African conglomerates - J. F. Affleck-Graves; G. H. Burt; J. M. Cleasby (South African Journal of Business Management, 1989)
Existant financial theory is unable to explain whether on aggregate conglomeration is beneficial to either individual shareholders or to the economy. Both advantages and disadvantages can be listed for the conglomeration process and it is thus an empirical question as to whether or not shareholders really do benefit from conglomeration. In this paper the long-term profitability of conglomerates is examined in an attempt to determine whether or not such shareholders earn superior returns on aggregate. This is done by contrasting the stock market performance of a sample of South African (SA) conglomerates over a six-year period with the performance of the overall market. In addition, their performance is contrasted with that of a random portfolio of non-conglomerate companies. Finally, a pseudo-conglomerate portfolio was constructed for each conglomerate in such a way that each portfolio had the same asset structure as its matched conglomerate. The performance of the conglomerates was then contrasted with that of the pseudo-conglomerate portfolio using market returns, return on assets, and return on equity. The results indicate that on aggregate, the conglomerates significantly underperform non-conglomerates. This is consistent with the view that conglomeration is in the interest of management rather than that of the shareholders.
Keywords: 650